EDUKASI PENCEGAHAN DIABETES MELITUS DENGAN MEDIA LEAFLET PADA WARGA KADIPATEN WETAN YOGYAKARTA - Paramesthi Sani, Siti; Dwi Jatmika, Septian Emma (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The incidence of diabetes mellitus is still common in Indonesia. The cause of people with diabetes mellitus is caused by an unhealthy lifestyle such as consuming excessive sugar, lack of physical activity and public knowledge about diabetes melitus. Based on the situation analysis conducted in the RT 024 Kadipaten Wetan area, the majority of people suffer from diabetes melitus with a percentage of 46%. This activity is carried out in 3 stages, namely the preparation, implementation and evaluation stages. The planning stage consists of situation analysis, determining problem priorities, problem solving alternatives. The implementation phase includes diabetes prevention education with door to door media leaflets for residents of RT 024 with a target of 15 families. The evaluation stage is carried out by conducting a pretest and posttest. The result is an increase in the knowledge of residents of RT 024 Kadipaten Wetan by 73%. It is hoped that this research can be continued by local health cadres so that the community can prevent diabetes melitus.